Manifestações clínicas e evolução da infecção pelo vírus da influenza A (H1N1) em receptores de transplante renal - Freitas, Tainá Veras de Sandes [UNIFESP] (2011)
INTRODUCTION: The emergence of the pan>demic outbreak of influenza A (H1N1) in April, 2009, represented a logistic challenge for public health. Although most infected patients presented clinical and evolutionary manifestations which were very similar to seasonal influenza, a significant number of individuals developed pneumonia and severe acute respiratory failure. The impact of influenza A (H1N1) in immunocompromised patients is not well established yet. METHODS: This study aimed to analyze the clinical presentations and evolution of influenza A (H1N1) in 19 kidney transplant recipients. Influenza A (H1N1) infection was confirmed by RT-PCR in all patients. Treatment included antiviral therapy with oseltamivir phosphate and antibiotics. RESULTS: The studied population was compounded mostly of white people (63%), males (79%), at a mean age of 38.6 ± 17 years and patients with at least one comorbidity (53%). Influenza A (H1N1) infection was identified 41.6 ± 49.6 months after transplantation. Common symptoms included cough (100%), fever (84%), dyspnea (79%), and myalgia (42%). Acute allograft dysfunction was observed in 42% of the patients. Five patients (26%) were admitted to the Intensive Care Unit, two (10%) required invasive ventilation support, and two (10%) required vasoactive drugs. Mortality rate was 10%. CONCLUSIONS: Acute renal allograft dysfunction was a common finding. Clinical, laboratory, and evolutionary characteristics were comparable to those in the general population.